Erythema Elevatum Diutinum - Chowdhury Satyendra Nath; Bandyopadhyay Debabrata (Wolters Kluwer Medknow Publications, 1997)
A patient with a three year history is presented as a classic example of erythema elevatum diutinum which responded to dapsone therapy.